ANALISA LAPORAN KEUANGAN PT KAPUAS PRIMA COAL Tbk. DARI SISI PROFITABILITAS SELAMA PANDEMI COVID-19 TAHUN 2020-2021 - Hajam Zakaria (Journal Accounting International Mount Hope, 2024)
The purposes of the research for the analysis of the financial report of PT KAPUAS PRIMA COAL Tbk. The method of quantitative research used in this paper is quantifiable. The results of research by calculating and estimating the Proportion of Productivity, the monetary relationships associated with the performance of the organization can be known. The collection of information in this research is carried out through the acquisition of financial report data obtained from the Indonesian Stock Exchange and writing research referring to the financial information of the organization. The exploration techniques in this paper are performed quantitatively with a proportional examination approach. Consequences of proportional estimates suggest that various monetary exposures can be said to have decreased during the Corona virus and have to be expanded again so that proportional positions can exceed normal business standards.